Three new species of Entomobryinae (Collembola, Entomobryidae) from Gansu, China - Zhou, Rong; Ma, Yitong (Zootaxa, 2022)
Three new species of Entomobryidae are described here. Willowsia trifascia sp. nov. is mainly characterised by its three longitudinal blue stripes on body and chaetotaxy of dorsal head. Himalanura gansuensis sp. nov. is the second species of the genus reported from China and characterised by its chaetotaxy, such as nine macrochaetae on Abd. I, and denticle on labral papilla. Homidia maijiensis sp. nov. is characterised for its yellow-green ground colour, labial base chaetae and dental spines.